2020
DOI: 10.3390/nano10102070
|View full text |Cite
|
Sign up to set email alerts
|

Topography: A Biophysical Approach to Direct the Fate of Mesenchymal Stem Cells in Tissue Engineering Applications

Abstract: Tissue engineering is a promising strategy to treat tissue and organ loss or damage caused by injury or disease. During the past two decades, mesenchymal stem cells (MSCs) have attracted a tremendous amount of interest in tissue engineering due to their multipotency and self-renewal ability. MSCs are also the most multipotent stem cells in the human adult body. However, the application of MSCs in tissue engineering is relatively limited because it is difficult to guide their differentiation toward a specific c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 260 publications
(430 reference statements)
1
84
0
Order By: Relevance
“…The strategy of combining biomaterial scaffolds with cells can be directed to various tissue injuries depending on the cell types applied. One of the most explored cell types in tissue engineering is the mesenchymal stromal cell (MSC), due to its differentiation potential, various isolation sources, low immunogenicity and high immunomodulatory potential ( Li et al, 2019 ; Cun and Hosta-Rigau, 2020 ; Wang et al, 2021 ). Along with MSCs, endothelial cells and their progenitors, such as the expanded CD133 + cell, are also crucial to tissue engineering due to their angiogenic potential ( Bongiovanni et al, 2014 ) and paracrine activity ( Angulski et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The strategy of combining biomaterial scaffolds with cells can be directed to various tissue injuries depending on the cell types applied. One of the most explored cell types in tissue engineering is the mesenchymal stromal cell (MSC), due to its differentiation potential, various isolation sources, low immunogenicity and high immunomodulatory potential ( Li et al, 2019 ; Cun and Hosta-Rigau, 2020 ; Wang et al, 2021 ). Along with MSCs, endothelial cells and their progenitors, such as the expanded CD133 + cell, are also crucial to tissue engineering due to their angiogenic potential ( Bongiovanni et al, 2014 ) and paracrine activity ( Angulski et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the same gure, note the di culty of nding the adhered cells being molded according to the surface on which they were exposed. Many works have found that cells have the ability to mold and modify their geometry depending on the environment [40].…”
Section: Discussionmentioning
confidence: 99%
“…80 Ongoing studies exhibits cell's behavior ranging affects from the adhesion of cell fluctuations to intracellular signaling pathway regulation that controls transcriptional activity and gene expression. 81 Traditionally, when considering bulk tissue properties, the nature of materials did not span the full range of biological length scale topography considered to affect cell activity (ranging from 10 nm to 100 μm). Nanophase reinforcements (such as HA-collagen nanocomposites or carbon nanotube-polymer nanocomposites) are now producing advances in bioactivity and mechanical properties such as flexural and compressive modules.…”
Section: Enhancing Materials Bio-functionalitymentioning
confidence: 99%